THE USING OF QUIZIZZ APPLICATION TO IMPROVE STUDENTS’ VOCABULARY OF TENTH GRADE STUDENTS OF SMA NEGERI 13 PANGKEP - Asti, Aisyah; Hamid, Radiah; andi baso, Farisha (English Language Teaching Methodology, 2024)
This study focuses on finding out the improvement of students' vocabulary by using Quizizz Application at the tenth grade students of SMA Negeri 13 Pangkep. This type of research is Pre-experimental research. The sample for this study was selected by consisting  of  28 students. The data from this study were obtained from the pre-test and post-test as a comparison material to determine the level of student improvement before and after using the Quizizz Application.The result of this research showed that the use of the Quizizz Application is very helpful for students in improving students' vocabulary mastery at Tenth Grade Students of SMA Negeri 13 Pangkep. This can be seen in how much improvement the student's scores are. This study shows the improvement that occurred in 24.34%. In addition, this is also supported by the data analysis results are the t-test value (7.73) is higher than the t-table value (1.703). By this result, it is concluded that there is a significant difference on students‟ vocabulary mastery before and after they are taught using Quizziz Aplication and it shows that application is effective to improve students’ vocabulary mastery.